NIMASA’s Lacunas in the Discharge of Its Regulatory Functions in the Management of Oil Spills Pollution in Nigeria - Akpan, Etuk Etiese (Advances in Social Sciences Research Journal, 2023)
Nigeria and Niger Delta region in particular have experienced environmental pollutions consequent from oil exploration and production activities. Fauna and flora as well as the entire marine ecosystem in these areas are at risk from oil spills pollution. Investigation to establish the indebt consequences of oil spill pollution on key performance indicators as well as the remedial actions for resuscitation is most times hinged on effective implementation, monitoring of the regulatory framework of the regulatory agencies saddled with such responsibilities. The overall success of which depends fully much on the environmental ambient and the enforcement capacity of the regulatory agencies. Effective maritime safety administration, maritime labor regulation, marine pollution prevention and control, search and rescue, inspections, cabotage enforcement, shipping development and ship registration, training and certification of seafarers, and maritime capacity development are the main focus of NIMASA as a governmental agency. However, all these specific roles are often not met due to certain lacunas within the corridors of the regulatory framework.